MANITOS TRABAJADORAS PARA DESARROLLAR LA MOTRICIDAD FINA EN NIÑOS DE 05 AÑOS DE EDAD DE LA I.E.I. N° 002 “RAQUEL ROBLES DE ROMÁN” CHACHAPOYASAMAZONAS, 2023 - Castañeda Labajos, Janeth Káterin (2023)
The present research report titled Working hands to develop fine motor skills in children 05 years of age of the I.E.I. N° 002 Raquel Robles de Román, Chachapoyas, Amazonas - 2023. N° 002 Raquel Robles de Román, Chachapoyas, Amazonas - 2023, has as purpose to demonstrate the influence of the workshop manitos trabajadoras in the development of fine motor skills in children of 5 years of age, developed within an applied research within the quantitative approach and focusing on a pre-experimental research design with a single group with entrance and exit test through a pre-test and post-test; having a population of 73 children in the age of 05 years and taking a sample of 26 children, of which the experimental work was carried out with 25 children of the age of 05 years; the proposed strategy was carried out in 20 workshops, being evaluated through a checklist to measure the progress of the proposed dimensions; the results show that children improved fine motor skills reaching the levels of achieved and outstanding; concluding that the strategy of working hands improves the levels of fine motor skills in children of 05 years. Key words: Motor skills; development; strengthening, variable, strategy.